Auditory gaydar: perception of sexual orientation based on female voice - Sulpizio, S. (2019)
We investigated auditory gaydar (i.e., the ability to recognize sexual orientation) in female speakers, addressing three related issues: whether auditory gaydar is (1) accurate, (2) language-dependent (i.e., occurs only in some languages, but not in others), and (3) ingroup-specific (i.e., occurs only when listeners judge speakers of their own language, but not when they judge foreign language speakers). In three experiments, we asked Italian, Portuguese, and German participants (total N = 466) to listen to voices of Italian, Portuguese, and German women, and to rate their sexual orientation. Our results showed that auditory gaydar was not accurate; listeners were not able to identify speakers’ sexual orientation correctly. The same pattern emerged consistently across all three languages and when listeners rated foreign-language speakers.